2021
DOI: 10.1111/febs.15824
|View full text |Cite
|
Sign up to set email alerts
|

A guide to the regulation of selective autophagy receptors

Abstract: Autophagy is a highly conserved catabolic process cells use to maintain their homeostasis by degrading misfolded, damaged and excessive proteins, nonfunctional organelles, foreign pathogens and other cellular components. Hence, autophagy can be nonselective, where bulky portions of the cytoplasm are degraded upon stress, or a highly selective process, where preselected cellular components are degraded. To distinguish between different cellular components, autophagy employs selective autophagy receptors, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
103
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 167 publications
2
103
0
1
Order By: Relevance
“…The observation that TAX1BP1 is major receptor for lysophagy extends recent work identifying roles for protein in various selective autophagic pathways (Gubas and Dikic, 2021) TAX1BP1 likely plays a dual role, as it interacts with both TBK1 and the RB1CC1-ULK1-ATG13 complex through its SKICH domain (Figure 8I). This may allow TAX1BP1 to orchestrate signaling via both of these kinase complexes, and could possibly promote autophagosome formation directly via recruitment of ULK1 to cargo (Ravenhill et al, 2019;Shi et al, 2020;Turco et al, 2020;Vargas et al, 2019) In addition, TAX1BP1 appears to have diverse cargo, ranging from membranous organelles as shown here to ubiquitylated protein aggregates as recently described (Sarraf et al, 2020).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The observation that TAX1BP1 is major receptor for lysophagy extends recent work identifying roles for protein in various selective autophagic pathways (Gubas and Dikic, 2021) TAX1BP1 likely plays a dual role, as it interacts with both TBK1 and the RB1CC1-ULK1-ATG13 complex through its SKICH domain (Figure 8I). This may allow TAX1BP1 to orchestrate signaling via both of these kinase complexes, and could possibly promote autophagosome formation directly via recruitment of ULK1 to cargo (Ravenhill et al, 2019;Shi et al, 2020;Turco et al, 2020;Vargas et al, 2019) In addition, TAX1BP1 appears to have diverse cargo, ranging from membranous organelles as shown here to ubiquitylated protein aggregates as recently described (Sarraf et al, 2020).…”
Section: Discussionsupporting
confidence: 77%
“…ERphagy), receptor proteins typically embedded in the cognate membrane are directly recognized by the autophagic machinery to facilitate engulfment in response to regulatory signals. These cargo receptors employ LC3-interacting region (LIR) motifs to associate with the LIR-docking site (LDS) in one or more of 6 ATG8 adaptor proteins that are located in the growing autophagosomal membrane by virtue of attachment to phosphatidylethanolamine via their C-terminal glycine residue (Gubas and Dikic, 2021;Johansen and Lamark, 2020). In contrast, Ub-dependent forms of organellophagy frequently employ a multistep process involving: 1) sensing of organelle damage, 2) ubiquitylation of one or more proteins associated with the membrane of the damaged organelle, 3) recruitment of one or more Ub-binding autophagy receptors containing LIR or other motifs that recruit autophagic machinery, and 4) expansion of the autophagic membrane around the organelle, thereby facilitating delivery to the lysosome (Gubas and Dikic, 2021;Johansen and Lamark, 2020;Khaminets et al, 2016;Lamark and Johansen, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macroautophagy (referred to as autophagy hereafter) is characterized by the formation of double-membrane vesicles, known as autophagosomes, which can engulf non-specific cellular material (bulk autophagy) or specific cargoes, such as protein aggregates or defective organelles (selective autophagy). After the fusion of autophagosomes with the lysosomes, the simple biochemical compounds generated during the degradation process are transported to the cytosol and reused for energy production or recycling (see recent reviews Lahiri et al, 2019 ; Melia et al, 2020 ; Gubas and Dikic, 2021 ). Autophagosome biogenesis is a highly regulated process involving different stages: induction, lipidation, and elongation of the autophagosome membrane (also known as the isolation membrane or phagophore), vesicle closure, and fusion with lysosomes.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, observations across multiple studies have revealed that many of the cargo receptors are not exclusive to one type of cargo but shared by many. For example, the most commonly studied adaptor protein, p62/SQSTM1, has been implicated in the turnover of a broad range of cargoes from peroxisomes, ER, and mitochondria to protein aggregates and bacteria ( 1 , 2 , 3 ). This is not unique to p62/SQSTM1, as Optineurin and Calcoco2/NDP52 have been shown to coordinate the turnover of not only multiple cargoes, but in some instances, the same type of cargo.…”
mentioning
confidence: 99%